2017
DOI: 10.1136/bmjopen-2016-014080
|View full text |Cite
|
Sign up to set email alerts
|

Integrated collaborative care teams to enhance service delivery to youth with mental health and substance use challenges: protocol for a pragmatic randomised controlled trial

Abstract: IntroductionAmong youth, the prevalence of mental health and addiction (MHA) disorders is roughly 20%, yet youth are challenged to access evidence-based services in a timely fashion. To address MHA system gaps, this study tests the benefits of an Integrated Collaborative Care Team (ICCT) model for youth with MHA challenges. A rapid, stepped-care approach geared to need in a youth-friendly environment is expected to result in better youth MHA outcomes. Moreover, the ICCT approach is expected to decrease service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
107
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 47 publications
4
107
0
2
Order By: Relevance
“…There is a general consensus that the current youth services system in Canada is fragmented [12345]. Researchers have identified that fragmentation of services is largely an issue related to program models failing to take context into account [3] as well as placing a focus on problems [1], and the overemphasis on siloed specialized services [13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a general consensus that the current youth services system in Canada is fragmented [12345]. Researchers have identified that fragmentation of services is largely an issue related to program models failing to take context into account [3] as well as placing a focus on problems [1], and the overemphasis on siloed specialized services [13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified that fragmentation of services is largely an issue related to program models failing to take context into account [3] as well as placing a focus on problems [1], and the overemphasis on siloed specialized services [13]. The historic and current approach takes an artificially segmented perspective of developing individuals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations